2013
DOI: 10.2514/1.t3980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Pipe Figure of Merit on an Evaporating Thin Film

Abstract: The performance of a two-phase heat transport device such as the loop heat pipe is influenced by the evaporative heat transfer coefficient in the evaporator. From previous experiments with loop heat pipes, it has been observed that fluids with a high heat pipe figure of merit have a high heat transfer coefficient. Considering an evaporating extended thin film, this paper theoretically corroborates this experimental observation by deriving a direct link between the evaporative heat flux at the interface and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Ammonia has the largest film thickness, followed by acetone, heptane and water, in a descending order. For the sake of comparison, it has also been shown that ammonia manifests the largest film thickness among those of acetone, pentane and octane, in a previous work employing nonpolar liquids without considering thermocapillary effect [12]. A pronounced deviation is induced by the thermocapillary effect on the film thickness such that the film thickness of Model 1 is larger than that of Model 2.…”
Section: Field Variables Of Working Fluidsmentioning
confidence: 92%
See 1 more Smart Citation
“…Ammonia has the largest film thickness, followed by acetone, heptane and water, in a descending order. For the sake of comparison, it has also been shown that ammonia manifests the largest film thickness among those of acetone, pentane and octane, in a previous work employing nonpolar liquids without considering thermocapillary effect [12]. A pronounced deviation is induced by the thermocapillary effect on the film thickness such that the film thickness of Model 1 is larger than that of Model 2.…”
Section: Field Variables Of Working Fluidsmentioning
confidence: 92%
“…In addition to the latent heat, other thermo-physical properties are also important in characterizing the evaporation process. Judging from this, the selection of appropriate working fluid for a designated range of operating temperature is an important issue in delineating the thermal performance of a two-phase cooling device [9][10][11][12][13]. By considering different types of common working fluid, it has been pointed out that the heat transport capacity of such device is dominated by the circulation rate, which is the ratio of the surface tension and dynamic viscosity of the working fluid [10,13].…”
Section: Introductionmentioning
confidence: 99%